Modelling the Survival of Acid-Adapted and Nonadapted Escherichia coli O157:H7 in Burkina: A Western African Traditional Fermented Milk Product - Donkor, L.; Affrifah, N.S.; Kunadu, A.P.H.; et al. (International Journal of Food Science, 2023)
Burkina, a traditional fermented dairy product, is consumed in most parts of West Africa, including Ghana. Studies on the microflora of Burkina have indicated the presence of Escherichia coli and other pathogenic organisms. Thus, predicting the survival of E. coli in the product will inform the best manufacturing and handling practices. This study investigated the combined effect of storage temperature and time on the survival of acid-adapted and acid-non-adapted E. coli O157:H7 in Burkina. Samples were pasteurised and inoculated with acid-adapted or acid-non-adapted E. coli O157:H7. They were stored at 5, 15, and 30° C for 0, 2, 4, 6, 8, 10, 12, 14, 18, and 48 h, and the bacteria colonies were enumerated. Growth rate (survival versus time) models were developed using MATLAB software. Observed data were fitted to the Baranyi model using the DMFit curve fitting software. The E. coli O157:H7 strain appeared inherently tolerant to acid, with storage time having the most significant effect on the response parameter, survival (log CFU/mL). A negative correlation was observed for the primary models (survival versus time), which accounted for 79-97% of the relationship (p < 0 05). Although E. coli survived, its growth was inhibited over time regardless of acid adaptation.
Research Article
Keywords: Burkina; Western African; Milk